Study of Chromium and Carbon Dopants Toward Erosive Wear Resistance of Planetary-Ball-Milled FeAl Intermetallic - Sebastian 13713002 , Jonathan
FeAl is recently used as an alternative to inner coating pipe in oil and gas industry as erosive wear protection. FeAl is a material known for high-temperature oxidation resistance, cheap to produce, high strength although it has low ductility. The effect of carbon and chromium doping was studied with its relations to erosive wear of FeAl. Fe-22 wt% Al was made with four variations of dopant composition: 0,1 wt% C, 0,5 wt% C, 0,1 wt% C + 1 wt% Cr and 0.5 wt% C + 1 wt% Cr. FeAl was processed using planetary ball milling of Fe and Al powders, followed by 90 kgf/cm2, 100 kgf/cm2 and 110 kgf/cm2 compaction pressure and sintering at 1250 oC. The material formed after milling was analyzed using X-Ray Diffraction and Scanning Electron Microscopy was used to determine shape and size of Fe and Al powders. Metallography was used to determine the porosity using image analysis. Erosive wear resistance is determined using Air Jet Erosion Tester. The result shows chromium and carbon dopants will reduce erosive wear resistance, where 1 wt% increase in carbon adds total mass loss by 0,0075 gram, 1 wt% chromium adds total mass loss by 0,0079 gram dan 1 % percentage porosity increase will add total mass loss by 0,0029 gram. In this experiment, doping affects more to erosive wear resitance of FeAl intermetallic than porosity